A computational analysis of hybrid nanofluids on heat transfer amelioration through a conical helical shell-and-tube heat exchanger under turbulent flow conditions - Mehdi Miansari; Fardin Nurpasand; Omid Ali Akbari; Hesam Moghadasi; Soheil Salahshour; Sh Baghaei (Case Studies in Thermal Engineering)
This research work examines the pressure drop and heat transfer trends within a conical helical tube heat exchanger utilizing pure water and hybrid nanofluids, namely Water/ Ag−HEG and Water/ MOS2−Fe3O4. The numerical simulation is performed using a Computational Fluids Dynamics (CFD) code in three-dimensional space according to the Finite Volume Method (FVM) for all examined cases. Also, turbulent flow regimes are conducted in this analysis employing the standard k–ε turbulence model, within the Dean Number (De) range of 2200 < De < 4250. In this regard, the proposed thermo fluids are evaluated under the same geometric and thermal conditions to assess their thermal performance parameters. Subsequently, the fluid exhibiting superior thermal performance is further analyzed at specific volume fractions. Results revealed that Water/ MOS2−Fe3O4 outperforms the other two fluids in terms of thermal performance, and the Nusselt Number for the hybrid nanofluid of Water/ MOS2−Fe3O4 is superior to that of water at diverse volume fractions of the nanofluids. Moreover, according to the outcomes, it was found that the pressure drop caused by the presence of the MOS2−Fe3O4 nanoparticles at volume fractions of 0.1 %, 0.3 %, and 0.5 % are 11 %, 19 %, and 20 % more than that of water, respectively. Thereby, the hybrid nanofluid of Water/ MOS2−Fe3O4 can be an alternative heat transfer fluid to conventional fluids in conical helical tube heat exchangers, improving heat transfer while maintaining an adequate pressure drop. Furthermore, as the Dean Number augments, the heat transfer coefficient (HTC) demonstrates an upward trend for all considered volume fractions of the hybrid nanofluids. Additionally, this phenomenon is ascribed to the intensified fluid velocity and interaction with the twisted wire, creating rotational and turbulent motion within the fluid, which leads to more frequent interaction between the coil wall and the fluid, therefore ameliorating the HTC between the two fluids which this value will be higher for nanofluids with a more significant volume fraction. At a constant Dean Number of 4250, the HTC was improved by approximately 200 % using hybrid nanofluid Water/ MOS2−Fe3O4 with a φ= 0.7 in comparison with pure water. Besides, the optimum thermal performance across all Dean Numbers is observed in models with volume fractions φ1 = φ2 = 0.7, peaking at about 2.72 for the hybrid nanofluid of Water/ MOS2−Fe3O4 at De = 3560.